OUTCOME OF ENDODONTIC PROCEDURES PERFORMED BY DENTAL INTERNS USING STAINLESS STEEL AND NiTi FILES: A 10- YEAR RETROSPECTIVE STUDY - Hasan, Arshad; Khan, Javeria Ali; Ali, Syed Abrar; Khan, Farhan Raza; Naz, Farah (Journal of Ayub Medical College Abbottabad, 2021)
Background: Preparation of root canal according to its desired anatomy and complete disinfection is a laborious task. Several factors influence the endodontic treatment including operator’s skill and knowledge, anatomy of the tooth, the instruments and equipment used. In the past stainless-steel instruments were used to prepare the root canal but it causes many iatrogenic errors. Nickel titanium instruments evolved to overcome the iatrogenic damages caused by stainless steel instruments. Keeping this in mind a comparative study was conducted on the clinical work of dental intern using stainless steel files and progressively taper nickel titanium instruments. The objective of this study was to compare the performance of interns using either stainless Steel or progressively tapered hand operated NiTi instruments. Methods: This retrospective study included post-treatment radiographs of root canal treatments performed by interns by using either stainless steel files or NiTi Protaper files, in the endodontic department of Hamdard University Dental Hospital, Karachi, Pakistan. It was a 10-year audit, from 2008 to 2018, of endodontic performance. A total of 1219 post treatment radiographs of good quality and showing at least 2mm periapical area beyond the root apex were included. In SS group, preparation were performed by step back method, while in NiTi group the Protaper instruments for hand were used. Scoring criteria was used to evaluate technical quality. The data was analysed using SPSS for windows version 17.0. Chi-square test was used to determine difference in proportions between the outcomes in SS and NiTi groups at p£0.05. Results: A total of 1219 radiographs were included out of which 584 (47.9%) belonged to SS and 635 (52.1%) to NiTi group. Overall satisfactory performance was in 553 (45.4%) teeth. Treatment done with NiTi was only marginally better than that achieved with SS files (NiTi n=298 (46.9%), SS n=255 (43.7%)). In the SS group, there were more overfills and internal and external transportation (p<0.001). NiTi reported more cases of inadequate lateral seal and separated instruments (p<0.05). Conclusion: Endodontic performance of interns was not improved with progressive taper NiTi manual instruments.